Web Site Presentation of Corporate Social Responsibility towards Customers Trust and Corporate Image - Selamat, Mohamad Hisyam; Saat, Rafeah Mat; Mohd Ali, Raja Haslinda Raja (International Journal of Economics and Financial Issues, 2016)
Corporate Social Responsibility (CSR) becomes an important tool to create a constructive relationship between companies and consumers. Companies use the potential of their web site in communicating CSR issues. This study aims to examine the role of web site presentation of CSR disclosure and its relationship with trust and corporate image. This study utilizes laboratory experiment with two hundred forty one respondent that are divided into two different groups of presentation richness. The results revealed that trusting belief and emotional trust are the antecedents in determining corporate image. The impacts of web site presentation richness on trust factors are mixed. The rich presentation on CSR has a significant influence on trusting belief and lean presentation has a strong influence on emotional trust. The findings could be used to assist the companies in communicating CSR actions and portray a good image among the consumers. Keywords: Trusting Belief, Emotional Trust, Corporate Image, Website Presentation, Media Richness JEL Classification: M14